2019
DOI: 10.1016/j.paid.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Person-task fit: Emotional consequences of performing divergent versus convergent thinking tasks depend on need for cognitive closure

Abstract: We investigated how people high (vs. low) in the Need for Cognitive Closure (NFC) experience working on divergent and convergent thinking tasks. Based on the notion of person-task fit we hypothesized that individuals high in NFC (but not those low in NFC) would feel less competent when solving divergent (vs. convergent) thinking tasks, because, being open-ended, divergent thinking tasks do not offer closure. We also predicted that, consequently, high NFC individuals would experience less positive emotions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Wronska et al [ 16 ] pointed to the importance of creativity in the psychological phenomena of people and highlighted the importance of creativity in the life of each person. Their study showed that participants high in NFC were less competent and felt more negative emotions when solving the divergent character tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Wronska et al [ 16 ] pointed to the importance of creativity in the psychological phenomena of people and highlighted the importance of creativity in the life of each person. Their study showed that participants high in NFC were less competent and felt more negative emotions when solving the divergent character tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Divergentthinking skills are one of the competencies that can be developed. Divergent thinking is the ability to find varied answers or solutions to a problem (Wronska et al, 2018). The skills are recognized as part of creativity in the formation and renewal of unique, original, and unreasonable ideas (Alfonso & Romo, 2016;Antink & Lederman, 2015).…”
mentioning
confidence: 99%
“…Second, NFC scales with emotional distress in both general populations (Berenbaum et al, 2008 ) and clinical populations with anxiety disorders (Freeman et al, 2006 ). For instance, self-reports of distress feelings, as well as cardiovascular measures (e.g., systolic blood pressure and heart rate), are increased in proportion with dispositional NFC in the decision-making processes (Wronska et al, 2019 ). Similarly, individuals scoring higher in the NFC experience more negative affect when they encounter an inconsistent (vs. consistent) cognition, regardless of whether the ultimate outcome is positive or negative (Di Santo et al, 2020 ; Wronska et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%